2015
DOI: 10.1002/2015je004894
|View full text |Cite
|
Sign up to set email alerts
|

History of the clay-rich unit at Mawrth Vallis, Mars: High-resolution mapping of a candidate landing site

Abstract: The Mawrth Vallis region is covered by some of the largest phyllosilicate‐rich outcrops on Mars, making it a unique window into the past history of Mars in terms of water alteration, potential habitability, and the search for past life. A landing ellipse had been proposed for the Curiosity rover. This area has been extensively observed by the High Resolution Imaging Science Experiment and the Compact Reconnaissance Imaging Spectrometer for Mars, offering the possibility to produce geologic, structural, and top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 39 publications
(105 reference statements)
2
39
0
Order By: Relevance
“…Based on their context and the existence of fractures and polygonal textures, proposed chloride-bearing materials have been inferred to originate from both ponding of surface runoff, and groundwater upwellings, followed by evaporation (Osterloo et al, 2010). Mg, Fe and sometimes Ca-sulfates are commonly detected in association with kilometer-thick Hesperian layered deposits (e.g., Gendrin et al, 2005;Flahaut et al, 2010Flahaut et al, , 2014Flahaut et al, , 2015 and polar dunes (Langevin et al, 2005, Massé et al, 2010, although more localized detections were also reported (e.g., Wray et al, 2011, Loizeau et al, 2015, Figure 9b). Although their origin is debated, the morphology and mineralogy of some sulfate salts (e.g., sulfate-rich depostis in Meridiani Planum), and their distribution in regions where groundwater upwellings are predicted, is consistent with an evaporitic origin (e.g., Ardvison et al, 2005;Andrews-Hanna et al, 2007;Osterloo et al, 2010, Davila et al, 2011.…”
Section: Relevance To Marsmentioning
confidence: 99%
“…Based on their context and the existence of fractures and polygonal textures, proposed chloride-bearing materials have been inferred to originate from both ponding of surface runoff, and groundwater upwellings, followed by evaporation (Osterloo et al, 2010). Mg, Fe and sometimes Ca-sulfates are commonly detected in association with kilometer-thick Hesperian layered deposits (e.g., Gendrin et al, 2005;Flahaut et al, 2010Flahaut et al, , 2014Flahaut et al, , 2015 and polar dunes (Langevin et al, 2005, Massé et al, 2010, although more localized detections were also reported (e.g., Wray et al, 2011, Loizeau et al, 2015, Figure 9b). Although their origin is debated, the morphology and mineralogy of some sulfate salts (e.g., sulfate-rich depostis in Meridiani Planum), and their distribution in regions where groundwater upwellings are predicted, is consistent with an evaporitic origin (e.g., Ardvison et al, 2005;Andrews-Hanna et al, 2007;Osterloo et al, 2010, Davila et al, 2011.…”
Section: Relevance To Marsmentioning
confidence: 99%
“…Because of their putative connection to river processes, sinuous ridges on Mars have been used to infer paleo-hydrology (Fassett and Head, 2005;Burr et al, 2010;Irwin et al, 2015), global history of water (Kite et al, 2015a, b), tectonics (Lefort et al, 2015), and large oceans or seas (DiBiase et al, 2013;Cardenas et al, 2017). In addition to being detectable and measurable from orbital data, they also are valuable to rover missions due to their presence in Gale Crater, the site of the Mars Science Laboratory rover (Anderson and Bell, 2010;Le Deit et al, 2013;Palucis et al, 2014), and in several sites of interest for future missions (e.g., Eberswalde crater (Irwin et al, 2015), Holden crater (Grant and Wilson, 2012), Jezero Crater (Goudge et al, 2018), Mawrth Valles (Loizeau et al, 2015), Melas Chasma (Williams and Weitz, 2014), and Aram Dorsum ).…”
mentioning
confidence: 99%
“…[], and morphologically similar Fe/Mg clay‐bearing units, likewise capped by non‐clay‐bearing darker‐toned material, are exposed in valley, chasma, and crater walls over a broad region to the west and southwest of Margaritifer [ Buczkowski et al ., , ; Le Deit et al ., ] and across the southern highlands [e.g., Mustard et al ., ; Adeli et al ., ; Goudge et al ., ]. In many cases these show layering similar to that in southern Ladon, for example, in Uzboi Vallis [ Grant et al ., ], Eberswalde crater [ Rice et al ., ], Noctis Labyrinthus [ Weitz et al ., ], Nili Fossae [ Mustard et al ., ; Ehlmann et al ., ], and Mawrth Vallis [ Michalski and Noe Dobrea , ; Loizeau et al ., ]. These layered units are often in channel walls or alluvial fans and are commonly attributed to detrital clay deposition or authigenic formation in an aqueous sedimentary context.…”
Section: Resultsmentioning
confidence: 99%
“…Goudge et al, 2015]. In many cases these show layering similar to that in southern Ladon, for example, in Uzboi Vallis , Eberswalde crater [Rice et al, 2013], Noctis Labyrinthus [Weitz et al, 2016a], Nili Fossae Ehlmann et al, 2009], and Mawrth Vallis [Michalski and Noe Dobrea, 2007;Loizeau et al, 2015]. These layered units are often in channel walls or alluvial fans and are commonly attributed to detrital clay deposition or authigenic formation in an aqueous sedimentary context.…”
Section: Hydrated Mineral-bearing Unitsmentioning
confidence: 96%